Rho GTPase Rac1: molecular switch within the galectin network and for N-glycan α2,6-sialylation/O-glycan core 1 sialylation in colon cancer in vitro - André, S; Singh, T; Lacal, J. C; Smetana, Karel; Gabius, H.-J (Folia biologica (Praha), 2014)
The Rho GTPase Rac1 is a multifunctional protein working through different effector pathways. The emerging physiological significance of glycanlectin recognition gives reason to testing the possibility for an influence of modulation of Rac1 expression on these molecular aspects. Using human colon adenocarcinoma (SW620) cells genetically engineered for its up- and down-regulation (Rac1+ and Rac1- cells) along with wild-type and mock-transfected control cells, the questions are addressed whether the presence of adhesion/growth-regulatory galectins and distinct aspects of cell surface glycosylation are affected. Proceeding from RT-PCR data to Western blotting after two-dimensional gel electrophoresis and flow cytofluorimetry with non-crossreactive antibodies against six members of this lectin family (i.e. galectins-1, -3, -4, -7, -8 and -9), a reduced extent of the presence of galectins-1, -7 and -9 was revealed in the case of Rac1 cells. Application of these six galectins as probes to determination of cell reactivity for human lectins yielded relative increases in surface labelling of Rac1- cells with galectins-1, -3 and -7. Examining distinct aspects of cell surface glycosylation with a panel of 14 plant/fungal lectins disclosed a decrease in α2,6-sialylation of N-glycans and an increase in PNA-reactive sites (i.e. non-sialylated core 1 O-glycans), two alterations known to favour reactivity for galectins-1 and -3. Thus, manipulation of Rac1 expression selectively affects the expression pattern within the galectin network at the level of proteins and distinct aspects of cell surface glycosylation.
Keywords: buněčná membrána; 2D gelová elektroforéza; regulace genové exprese u nádorů; Humans; messenger RNA; nádory tračníku; Colonic Neoplasms; polymerázová řetězová reakce s reverzní transkripcí; Phenotype; lektiny; N-Acetylneuraminic Acid; lidé; Reverse Transcriptase Polymerase Chain Reaction; Galectins; galektiny; rac1 GTP-Binding Protein; RNA, Messenger; Lectins; glykosylace; Flow Cytometry; fenotyp; Electrophoresis, Gel, Two-Dimensional; nádorové buněčné linie; průtoková cytometrie; rac1 protein vázající GTP; Cell Membrane; kyselina N-acetylneuraminová; Cell Line, Tumor; polysacharidy; Polysaccharides; Gene Expression Regulation, Neoplastic; Glycosylation